Synthesis of substituted tetrahydro-1H-xanthen-1-ones and xanthenes - Patil, M. L.; Borate, Hanumant B. (Journal of Chemical Research, 2005)
A short and an efficient methodology for the synthesis of substituted tetrahydro-1H-1-xanthenones and xanthenes is described.
Keywords: balanol; diarylmethanes; tetrahydro-1H-xanthen-1-ones; Xanthenes

Efficient synthesis of 1,8-dioxo-octahydro-xanthene derivatives promoted by a room temperature ionic liquid at ambient conditions under ultrasound irradiation - Venkatesan, K.; Pujari, Suresh S.; Lahoti, Rajgopal J.; Srinivasan, K. V. (Ultrasonics Sonochemistry, 2008)
The condensation reaction involving an aldehyde and diketone was efficiently promoted by the Ionic liquid, [Hbim]BF(4) (IL) as a reaction medium with methanol as co-solvent at ambient temperature under ultrasonic irradiation to afford the corresponding 1,8-dioxo-octahydroxantliene (xanthene) derivatives in excellent yields. The advantages of this method include among others the use of a recyclable, non-volatile ionic liquid, which promotes this protocol under ambient temperature without the requirement of ally added catalyst. The reaction times and yields are compared with p-TSA catalyzed synthesis of xanthenes under thermal conditions, which is also reported for the first time under our reaction conditions. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: aldehydes; ambient conditions; Bronsted acidity; dimedone; Ionic liquid; Ultrasound; Xanthenes

Synthesis and in vitro study of 14-aryl-14H-dibenzo[a.j]xanthenes as cytotoxic agents - Bhattacharya, Asish K.; Rana, Kalpeshkumar C.; Mujahid, Mohammad; Sehar, Irum; Saxena, Ajit K. (Bioorganic & Medicinal Chemistry Letters, 2009)
A simple and expedient method for the synthesis of a series of 14-aryl-14H-dibenzo[a.j]xanthenes is described through a one-pot condensation of beta-naphthol with aryl aldehydes catalysed by TaCl(5) under solvent-free conventional heating. The major advantages of the present method are: high yields, less reaction time, solvent-free condition and easy purification of the products. The synthesized 14-aryl-14H-dibenzo[a.j]xanthenes were evaluated against a panel of six human cancer lines of different tissues. Synthesized compound 30 showed IC(50) of 37.9 and 41.3 mu M against Colo-205 and 502713, respectively, whereas 3g showed IC(50) of 41.9 mu M against Colo-205. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Aldehyde; beta-Naphthol; condensation; Cytotoxicity; One-pot reaction; Solvent-free; Tantalum(V) chloride; Xanthenes